1975
DOI: 10.1149/1.2134041
|View full text |Cite
|
Sign up to set email alerts
|

Polaromicrotribometry: A Friction Method for the Study of Polarized Metal Solution Interfaces: Application to the Gold Electrode

Abstract: A new adaptation of the technique of mechanical friction is proposed for the study of metal solution interfaces in electrochemistry. The coefficient of friction, especially sensitive to surface-state changes, is measured by means of a micro-slider, which does not disturb the i-v electrochemical curves. This method, called polaromicrotribometry, is easy to employ and of general application. It permits the measurement of electrochemical transient phenomena as well as stationary ones, in aqueous and organic elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…They showed how the friction versus potential curve could be explained in terms of double layer repulsion [53,54]. In 1975, Dubois and Lacaze proposed measurement of the change in friction with electrode potential as a method for studying metal solution interfaces in electrochemistry, a technique they termed polaromicrotribology [55].…”
Section: Research On Aqueous Systemsmentioning
confidence: 99%
“…They showed how the friction versus potential curve could be explained in terms of double layer repulsion [53,54]. In 1975, Dubois and Lacaze proposed measurement of the change in friction with electrode potential as a method for studying metal solution interfaces in electrochemistry, a technique they termed polaromicrotribology [55].…”
Section: Research On Aqueous Systemsmentioning
confidence: 99%
“…The friction coefficient has also been examined at electrode surfaces. Early applications of polaromicrotribometry, which involved the simultaneous measurement of surface friction and electrochemistry, indicated that friction and wear at metal and metal oxide interfaces varied with electrode potential. , The potential dependence of the friction coefficient between a platinum slider and wire showed a parabolic dependence that exhibited a maximum at the potential of zero charge . A recent AFM study of the friction force at graphitic steps showed a variation with electrode potential that suggested an electrostatic component dominated this process …”
Section: Introductionmentioning
confidence: 99%
“…Aside from infrared and XPS spectroscopies, we have developed a new means of analyzing the metal-solution interface, called polaromicrotribometry or PMT (8,9). This technique, based on the measurement and recording of a friction coefficient between the electrode surface and a microslider, has proved to be particularly well adapted to the study of the formation of oxide layers (10), organic films (11,12) and, more recently, to adsorbed layers (13,14).…”
mentioning
confidence: 99%